Influence of staggered sowing, planting ratio and subtending cob leaf clipping on seed quality parameters of maize - VINUTHA, K. S.; S. RAJENDRA PRASAD; RAME GOWDA; P. RAVISHAKAR; PARASHIVAMURTHY; S.P. JEEVAN KUMAR (Seed Research, 2026)
To know the quality of seed produced by different agronomic practices viz., staggered sowing, planting ratio and subtending cob leaf clipping in single cross maize hybrid Hema was carried out. Seeds harvested from staggered sowing S, (sowing of male 3 days earlier to female) resulted in significantly higher 100 seed weight (31.39 g), seedling length (35.86 cm), seedling dry weight (86.93 mg), total dehydrogenase activity of seed (1.43, A450), seedling vigour index-I (3165) and seedling vigour index-II (7711). However, the germination percentage, electrical conductivity of seed leachate, pH of seed leachate and seed health was found insignificant for planting ratio and subtending cob leaf clipping and their interaction. It is clearly illustrated that the seeds from sowing of male 3 days earlier to female (S₂) has showed better seed quality in hybrid Hema may be due to the timely seed setting and maturity.